2018
DOI: 10.1002/fes3.145
|View full text |Cite
|
Sign up to set email alerts
|

Root imaging showing comparisons in root distribution and ontogeny in novel Festulolium populations and closely related perennial ryegrass varieties

Abstract: The incorporation of new sophisticated phenotyping technologies within a crop improvement program allows for a plant breeding strategy that can include selections for major root traits previously inaccessible due to the challenges in their phenotype assessment. High-throughput precision phenotyping technology is employed to evaluate root ontogeny and progressive changes to root architecture of both novel amphiploid and introgression lines of Festulolium over four consecutive months of the growing season and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Selective grass breeding has been conducted on LmFg BC 2 introgression lines on the basis of their heat and drought tolerance toward producing a more stress-tolerant and current UK National Listed variety; AberLink (Humphreys, Harper, Armstead, & Humphreys, 2005a;APHA, 2017). Hence, they may be viewed as possible alternatives to the use of seed mixtures, or for a specialist use such as in drought-prone regions or in preventing flooding due to deep rooting, for example, MacLeod et al, (2007); MacLeod et al 2013; Humphreys et al (2018). Theoretically, the hybridization of nutritionally desirable Lolium with stress-tolerant Festuca species would not only help protect the crop in a harsh field environment but could affect the cellular responses on exposure to the adverse conditions of the rumen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selective grass breeding has been conducted on LmFg BC 2 introgression lines on the basis of their heat and drought tolerance toward producing a more stress-tolerant and current UK National Listed variety; AberLink (Humphreys, Harper, Armstead, & Humphreys, 2005a;APHA, 2017). Hence, they may be viewed as possible alternatives to the use of seed mixtures, or for a specialist use such as in drought-prone regions or in preventing flooding due to deep rooting, for example, MacLeod et al, (2007); MacLeod et al 2013; Humphreys et al (2018). Theoretically, the hybridization of nutritionally desirable Lolium with stress-tolerant Festuca species would not only help protect the crop in a harsh field environment but could affect the cellular responses on exposure to the adverse conditions of the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Grasses were harvested at the same hour (15:00hr) having a target maturity of reproductive stage R1index 3.1 (Moore & Moser, 1995). Selection of these cultivars was based on previous evidence of potential advantages as cultivar or individual genotypes in terms of protein stability and thermotolerance where F. arundinacea var glaucescens had been shown previously to have slower rates of endogenous protein degradation than L. perenne, and F. mairei is one of the most heat tolerant fescues (Humphreys et al, 2014(Humphreys et al, , 2018MacLeod et al, 2013). All cultivars used were 4x as it was shown by Humphreys et al (2014) that a balanced Lolium: Festuca genome was required for expression of the slow proteolysis trait.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in new root screening technologies have provided opportunities for the incorporation of selections for root growth and design in plant breeding strategies. The differences in root architecture and changes in the ontogeny of certain Festulolium cultivars through the growing season have been described elsewhere and compared to currently used perennial ryegrass varieties during equivalent timelines (Macleod et al, 2013 and Humphreys et al, 2018). Humphreys et al (2018) found that certain Festulolium hybrids had more extensive root systems, particularly at depth, when compared to Lolium perenne L. (perennial ryegrass).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in root architecture and changes in the ontogeny of certain Festulolium cultivars through the growing season have been described elsewhere and compared to currently used perennial ryegrass varieties during equivalent timelines (Macleod et al, 2013 and Humphreys et al, 2018). Humphreys et al (2018) found that certain Festulolium hybrids had more extensive root systems, particularly at depth, when compared to Lolium perenne L. (perennial ryegrass). Such deeper root systems should improve water (Durand et al, 2007) acquisition and aide soil hydrology (MacLeod et al, 2013) and carbon sequestration at depth in soils (Kell, 2011).…”
Section: Introductionmentioning
confidence: 99%